Micro-nano silver powder and preparation method and application thereof
Through electrostatic self-assembly technology, negatively charged and positively charged silver nanocrystals are mixed to prepare small-sized micro-nano silver powder with excellent conductivity and sintering activity, which solves the problems of complex micro-nano silver powder preparation process and poor performance in the existing technology, and achieves efficient improvement of the conductive paste performance of photovoltaic cells.
Patent Information
- Application Number
- CN202510005051.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to effectively prepare micro-nano silver powder with excellent electrical conductivity, sintering activity and controllable morphology, and the preparation process is complex and difficult to be applied to large-scale industrial production.
By preparing a silver nanocrystalline solution and performing acidic and alkaline adjustments respectively to obtain a negatively charged and positively charged silver nanocrystalline solution, the two were then mixed for electrostatic self-assembly to prepare micro-nano silver powder with different morphology.
It realizes the efficient preparation of micro-nano silver powder, has excellent low-temperature sintering activity, rheology and conductivity, and is suitable for conductive pastes of photovoltaic cells, significantly improving the photoelectric conversion efficiency.
Smart Images

Figure CN119703046A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of silver powder preparation, and specifically to micro-nano silver powder and its preparation method and application. Background Art
[0002] Photovoltaic cells, as a new type of clean energy that can replace traditional fossil energy, have attracted widespread attention. Among them, conductive paste is an important component of photovoltaic cells and affects the photoelectric conversion rate of photovoltaic cells. Silver powder is considered to be an important conductive phase of photovoltaic cell conductive paste due to its excellent conductivity, ductility, controllable microstructure and modifiable surface environment. The morphology and particle size distribution of micro-nano silver powder determine the performance of the conductive paste. Due to the small particle size, large specific surface area and high surface energy of micro-nano silver powder, it is difficult to prepare. At present, chemical methods are mainly used to prepare silver powder, such as microwave method, hydrothermal reduction method, chemical deposition method, microemulsion method, thermal decomposition method, spray pyrolysis method, etc. However, these methods have the disadvantages of harsh reaction conditions, high requirements for reaction equipment, and cumbersome preparation process, which are difficult to apply to industrial mass production. In addition, the silver powder prepared by the above method is not good in terms of morphology, size, specific surface area, particle size distribution and dispersibility, and it is difficult to effectively improve the conductivity, sintering activity, fineness and resistivity of the conductive silver paste. Therefore, the preparation technology of micro-nano silver powder needs to be further improved. Summary of the invention
[0003] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present application proposes a micro-nano silver powder with excellent low-temperature sintering activity, rheological properties, and electrical conductivity, and a preparation method and application thereof.
[0004] The first aspect of the present application provides a method for preparing micro-nano silver powder, comprising:
[0005] preparing a silver nanocrystal solution;
[0006] Mixing the silver nanocrystal solution with an acidic regulator to obtain a silver nanocrystal solution with a negative charge;
[0007] The silver nanocrystal solution is mixed with an alkaline regulator to obtain a silver nanocrystal solution with a positive charge;
[0008] The negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution are mixed to obtain the micro-nano silver powder.
[0009] The method described in the present application has a simple preparation process, and the morphology of the prepared micro-nano silver powder is easy to control, and it has good sintering activity and conductivity. Using it as the conductive phase of the conductive paste of photovoltaic cells can greatly improve the photoelectric conversion efficiency.
[0010] In some embodiments, the morphology of the micro-nano silver powder includes at least one of a spherical structure, a cubic structure, a polyhedral structure, and a lamellar structure. Thus, the morphology of the micro-nano silver powder is easy to control.
[0011] In some embodiments, the mass ratio of the negatively charged silver nanocrystals to the positively charged silver nanocrystals is 1:0.2-3. This can make the reaction more complete and is conducive to obtaining micro-nano silver powders with different morphologies.
[0012] In some embodiments, the pH of the negatively charged silver nanocrystal solution is 3-5.
[0013] In some embodiments, the concentration of the negatively charged silver nanocrystal solution is 1 g / L to 5 g / L.
[0014] In some embodiments, the pH of the positively charged silver nanocrystal solution is 9-11.
[0015] In some embodiments, the concentration of the positively charged silver nanocrystal solution is 1 g / L to 5 g / L.
[0016] Within the above pH and concentration ranges, it is favorable for the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution to self-assemble into micro-nano silver particles with different morphologies through electrostatic self-assembly.
[0017] In some embodiments, the acidic regulator includes at least one of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, nonanoic acid, capric acid, tartaric acid, oleic acid, ricinoleic acid, linoleic acid, stearic acid, palmitic acid, tetradecanoic acid, lauric acid, lactic acid, fumaric acid, and uric acid. Thus, the material source is wide, which is conducive to obtaining a negatively charged silver nanocrystal solution.
[0018] In some embodiments, the alkaline regulator includes at least one of ammonia water and organic amines; the organic amines include at least one of ethylenediamine, dodecylamine, hexadecylamine, octadecylamine, triethylamine, and triethanolamine. Thus, the material source is wide, which is conducive to obtaining a positively charged silver nanocrystal solution.
[0019] In some embodiments, the silver nanocrystal solution is prepared by the following steps: mixing an aqueous silver nitrate solution, a dispersant, and a reducing agent, and subjecting the obtained mixture to a reduction reaction to obtain the silver nanocrystal solution.
[0020] In some embodiments, the dispersant includes at least one of polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol, thereby improving the dispersibility of the silver nanocrystal solution and making the silver nanocrystals more uniform.
[0021] In some embodiments, the reducing agent includes at least one of citric acid, sodium citrate, ethylene glycol, formaldehyde, and hydrogen peroxide, wherein the concentration of the solution prepared by the reducing agent is 0.1 mol / L to 0.5 mol / L. This is conducive to reducing the silver ions in the silver nitrate aqueous solution to silver element.
[0022] In some embodiments, the reaction temperature of the reduction reaction is 25°C to 100°C; in other embodiments, the reaction is carried out by heating to boiling state at normal pressure, thereby facilitating the reaction and improving the efficiency of the reduction reaction.
[0023] In some embodiments, mixing the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution comprises: adding the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution to a reaction container at the same time and stirring. The two silver nanocrystals are injected and mixed for the same length of time, so that the negatively charged silver nanocrystals and the positively charged silver nanocrystals added successively can synchronously attract each other, assemble quickly, and align in a directional manner, so as to grow silver particles with uniform particle size, controllable morphology, and high dispersibility.
[0024] In some embodiments, the addition speed of the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution is independently 10 mL / min to 100 mL / min. If the addition speed is too slow, the reaction efficiency is low and the production cost is high; if the addition speed is too fast, the reaction control is difficult, and the morphology and particle size of the product are messy and uncontrollable. Within the above addition speed range, it is beneficial to improve the reaction efficiency and regulate the product morphology.
[0025] In some embodiments, the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution are stirred at a speed of 2000 rpm to 10000 rpm, thereby facilitating the improvement of the self-assembly rate of the silver nanocrystals.
[0026] The second aspect of the present application provides a micro-nano silver powder, which is prepared by the method described in the first aspect of the present application. Therefore, the micro-nano silver powder has excellent low-temperature sintering activity, rheological properties and electrical conductivity.
[0027] In some embodiments, the particle size of the micro-nano silver powder is 100 nm to 500 nm, and the specific surface area is 0.8 m 2 / g~1.2m 2 / g. Thus, the dispersibility of the micro-nano silver powder can be further improved.
[0028] The third aspect of the present application provides a conductive paste, which contains the micro-nano silver powder described in the second aspect of the present application. Therefore, the conductive paste has good fluidity and conductivity.
[0029] The fourth aspect of the present application provides a battery, comprising a metal electrode, wherein the metal electrode comprises the micro-nano silver powder described in the second aspect of the present application or is prepared from the conductive paste described in the third aspect of the present application. Thus, the battery has a high conversion efficiency.
[0030] The beneficial effects of this application are:
[0031] (1) The scheme of the present application uses silver nitrate as a raw material, obtains ultra-small-sized silver nanocrystal primary building blocks through a simple one-step chemical reduction method, and then modifies the surface with positive and negative charges respectively, and then self-assembles into nanosilver with different morphological structures through mixed electrostatic self-assembly, which improves the fluidity of the conductive paste while increasing the sintering activity and reducing the sintering temperature;
[0032] (2) The method provided in this application is relatively simple, the preparation process is simple, and the morphology of the silver powder is easy to control;
[0033] (3) The method provided in this application has high raw material utilization rate, short reaction time and strong repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a process roadmap for preparing the micro-nano silver powder of the embodiment of the present application.
[0035] Figure 2 This is a TEM photograph of the ultra-small silver nanocrystals of Example 1 of the present application.
[0036] Figure 3 This is the XRD spectrum of the micro-nano silver powder of Example 1 of the present application.
[0037] Figure 4 This is a SEM photograph of the micro-nano silver powder of Example 1 of the present application.
[0038] Figure 5 This is a SEM photograph of the micro-nano silver powder of Example 2 of the present application.
[0039] Figure 6 This is a SEM photograph of the micro-nano silver powder of Example 3 of the present application.
[0040] Figure 7 This is a SEM photograph of the micro-nano silver powder of Example 4 of the present application.
[0041] Figure 8 This is a SEM photograph of the micro-nano silver powder of Example 5 of the present application.
[0042] Fig. 9 This is a SEM photograph of the micro-nano silver powder of Example 1 of the present application sintered at 140° C. for 30 minutes.
[0043] Fig.10 This is the XRD spectrum of the micro-nano silver powder of Comparative Example 1 of the present application.
[0044] Fig.11 This is a SEM photograph of the micro-nano silver powder of Comparative Example 1 of the present application.
[0045] Fig.12 This is a SEM photograph of the micro-nano silver powder of Comparative Example 1 of the present application sintered at 140° C. for 30 minutes.
[0046] Fig.13 This is a SEM photograph of the micro-nano silver powder of Comparative Example 1 of the present application sintered at 180° C. for 30 minutes. DETAILED DESCRIPTION
[0047] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0048] The first aspect of the present application provides a method for preparing micro-nano silver powder, comprising:
[0049] S1: preparing silver nanocrystal solution.
[0050] In some embodiments, the silver nanocrystal solution is prepared by the following steps: mixing an aqueous silver nitrate solution, a dispersant, and a reducing agent, and subjecting the obtained mixture to a reduction reaction to obtain the silver nanocrystal solution.
[0051] In some embodiments, the dispersant includes at least one of polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol, thereby improving the dispersibility of the silver nanocrystal solution and making the silver nanocrystals more uniform.
[0052] In some embodiments, the reducing agent includes at least one of citric acid, sodium citrate, ethylene glycol, formaldehyde, and hydrogen peroxide, wherein the concentration of the reducing agent solution is 0.1 mol / L to 0.5 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L, etc. Thus, it is beneficial to reduce silver ions to silver element.
[0053] In some embodiments, the reaction temperature of the reduction reaction is 25°C to 100°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, etc. In other embodiments, the reaction can be carried out by heating to boiling state at normal pressure.
[0054] Specifically, in this step, silver nanocrystals are prepared by liquid phase chemical reduction method: a silver nitrate aqueous solution is prepared, a reducing agent solution is added thereto to initiate a reduction reaction, and a silver nanocrystal solution is obtained.
[0055] S2: mixing the silver nanocrystal solution with an acidic regulator to obtain a silver nanocrystal solution with a negative charge.
[0056] Specifically, the silver nanocrystal solution prepared above can be weighed and added with an acidic regulator containing carboxylic acid, and then stirred to obtain a silver nanocrystal solution B1 with a negative charge.
[0057] In some embodiments, the acidic regulator includes at least one of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, nonanoic acid, capric acid, tartaric acid, oleic acid, ricinoleic acid, linoleic acid, stearic acid, palmitic acid, tetradecanoic acid, lauric acid, lactic acid, fumaric acid, and uric acid. Thus, the material source is wide, which is conducive to obtaining a negatively charged silver nanocrystal solution.
[0058] In some embodiments, the pH of the negatively charged silver nanocrystal solution is 3-5 (eg, 3, 4, or 5, etc.).
[0059] In some embodiments, the concentration of the negatively charged silver nanocrystal solution is 1 g / L to 5 g / L (eg, 1 g / L, 2 g / L, 3 g / L, 4 g / L, or 5 g / L, etc.).
[0060] S3: mixing the silver nanocrystal solution with an alkaline regulator to obtain a silver nanocrystal solution with a positive charge.
[0061] Specifically, the silver nanocrystal solution prepared above can be weighed and an alkaline regulator solution containing amine can be added thereto, and the mixture can be stirred to obtain a silver nanocrystal solution C1 with positive charges on the surface.
[0062] In some embodiments, the alkaline regulator includes at least one of ammonia water and organic amines; the organic amines include at least one of ethylenediamine, dodecylamine, hexadecylamine, octadecylamine, triethylamine, and triethanolamine. Thus, the material source is wide, which is conducive to obtaining a positively charged silver nanocrystal solution.
[0063] In some embodiments, the pH of the positively charged silver nanocrystal solution is 9-11 (eg, 9, 10, or 11, etc.).
[0064] In some embodiments, the concentration of the positively charged silver nanocrystal solution is 1 g / L to 5 g / L (eg, 1 g / L, 2 g / L, 3 g / L, 4 g / L, or 5 g / L, etc.).
[0065] S4: mixing the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution to obtain the micro-nano silver powder.
[0066] In some embodiments, the mass ratio of the negatively charged silver nanocrystals to the positively charged silver nanocrystals is 1:0.2-3, for example, 1:0.2, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5 or 1:3. This can make the reaction more complete, which is conducive to obtaining micro-nano silver powders with different morphologies. Specifically, ① when the mass of the negatively charged silver nanocrystals is equal to the mass of the positively charged silver nanocrystals, the silver nanocrystals are self-assembled by electrostatics to obtain micro-nano silver particles with a spherical structure; ② when the mass of the negatively charged silver nanocrystals is greater than the mass of the positively charged silver nanocrystals, the silver nanocrystals are self-assembled by electrostatics to obtain micro-nano silver particles with a cubic or polyhedral structure; ③ when the mass of the negatively charged silver nanocrystals is less than the mass of the positively charged silver nanocrystals, the silver nanocrystals are self-assembled by electrostatics to obtain micro-nano silver particles with a lamellar structure. The two types of silver nanocrystals are injected and mixed for the same length of time, so that the negatively charged silver nanocrystals and the positively charged silver nanocrystals added successively can attract each other synchronously, assemble quickly, and arrange in a direction, growing silver particles with uniform particle size, controllable morphology and high dispersion.
[0067] In some embodiments, mixing the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution comprises: adding the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution into a reaction container at the same time and stirring.
[0068] In some embodiments, the addition speed of the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution is independently 10 mL / min to 100 mL / min, for example, 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min or 100 mL / min. If the addition speed is too slow, the reaction efficiency is low and the production cost is high; if the addition speed is too fast, the reaction control is difficult, and the morphology and particle size of the product are messy and uncontrollable. Within the above addition speed range, it is beneficial to improve the reaction efficiency and regulate the product morphology.
[0069] In some embodiments, the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution are stirred at a speed of 2000 rpm to 10000 rpm, for example, 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm or 10000 rpm, etc. After stirring, the two silver nanocrystals are self-assembled into silver particles by electrostatics.
[0070] In some embodiments, before obtaining the micro-nano silver powder, centrifugation, water washing and drying are required, which is helpful to improve the purity of the micro-nano silver powder.
[0071] In some embodiments, the centrifugal rotation speed is 2000rpm~10000rpm, for example, it can be 2000rpm, 3000rpm, 4000rpm, 5000rpm, 6000rpm, 7000rpm, 8000rpm, 9000rpm or 10000rpm; the drying temperature is -10℃~60℃, for example, it can be -10℃, 0℃, 10℃, 20℃, 30℃, 40℃, 50℃ or 60℃.
[0072] The second aspect of the present application provides a micro-nano silver powder, which is prepared by the method described in the first aspect of the present application. Therefore, the micro-nano silver powder has excellent low-temperature sintering activity, rheological properties and electrical conductivity.
[0073] In some embodiments, the particle size of the micro-nano silver powder is 100 nm to 500 nm (such as 100 nm, 200 nm, 300 nm, 400 nm or 500 nm, etc.), and the specific surface area is 0.8 m 2 / g~1.2m 2 / g(such as 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g or 1.2m 2 / g, etc.). Since the silver crystals grow synchronously through self-assembly during the synthesis process, the obtained silver powder has uniform particle size and high dispersibility; the surface of the silver powder particles is smooth, and the specific surface area of the silver powder of 100nm to 500nm can reach 0.8m 2 / g~1.2m 2 / g, which is beneficial to improving the fluidity of the conductive paste; at the same time, the micro-nano silver powder described in the present application has a small grain size, uniformly distributed active sites, and high sintering activity.
[0074] In this article, the particle size test method of micro-nano silver powder is: take a microscopic picture of silver powder with a scanning electron microscope, and statistically analyze the average particle size data of the particle size in the electron microscope picture. Specifically, the common image processing software can be used to binarize and accurately measure and calculate the average particle size. The specific surface area refers to the total area per unit mass of micro-nano silver powder. The test method is the low-temperature nitrogen adsorption method, which is one of the most widely used methods. This method is based on the BET theory. At liquid nitrogen temperature, nitrogen molecules are adsorbed on the sample surface, and the specific surface area is calculated by measuring the adsorption amount.
[0075] The third aspect of the present application provides a conductive paste, which contains the micro-nano silver powder described in the second aspect of the present application. Therefore, the conductive paste has good fluidity and conductivity.
[0076] The fourth aspect of the present application provides a battery, comprising a metal electrode, wherein the metal electrode comprises the micro-nano silver powder described in the second aspect of the present application or is prepared from the conductive paste described in the third aspect of the present application. As an example, the battery can be a photovoltaic cell. Thus, the battery has a high conversion efficiency.
[0077] The present application assembles ultra-small-sized silver nanocrystal primary building blocks into micro-nano silver powders with different morphological structures through the method of chemical reduction-electrostatic self-assembly, thereby improving the fluidity, sintering activity and conductivity of the conductive paste. Using it as the conductive phase of the battery conductive paste can greatly improve the photoelectric conversion efficiency.
[0078] The embodiments of the present application are described in detail below.
[0079] Example 1
[0080] (1) Preparation of ultra-small silver nanocrystals:
[0081] Add 50 mg of polyvinyl pyrrolidone, 1.92 g of citric acid and 1.7 g of AgNO3 to 200 mL of deionized water and continue stirring at room temperature until completely dissolved. Then, heat the mixed solution to boiling and quickly add 200 μL of 0.5 mol L -1 Ascorbic acid solution was used to initiate the reduction reaction, and stirring was continued for 1 hour to obtain a silver nanocrystal solution with ultra-small size of 1nm to 50nm;
[0082] (2) Surface charge modification of silver nanocrystals:
[0083] 200 mL of the silver nanocrystal solution in step (1) is measured, and about 1 mL of acetic acid solution is added thereto to adjust the pH of the solution to 4, and the mixture is stirred for 1 h to obtain carboxyl silver nanocrystals with negative charges on the surface; similarly, 200 mL of the silver nanocrystal solution in step (1) is measured, and about 1 mL of ethylenediamine solution is added thereto to adjust the pH of the solution to 10, and the mixture is stirred for 1 h to obtain amine silver nanocrystals with positive charges on the surface;
[0084] (3) Assembly and preparation of micro-nano silver powder:
[0085] 100 mL of the silver nanocrystal solution with negative surface charge prepared in step (2) and 100 mL of the silver nanocrystal solution with positive surface charge (mass ratio of 1:1) were added into a 250 mL beaker at the same flow rate (20 mL / min), and the silver nanocrystals with different electronegativity underwent electrostatic self-assembly under magnetic stirring (rotation speed of 5000 rpm), and then centrifuged, washed with water, and vacuum dried to obtain spherical micro-nano silver powder.
[0086] Example 2
[0087] (1) Same as step (1) of Example 1;
[0088] (2) Same as step (2) of Example 1;
[0089] (3) 150 mL of silver nanocrystals with negative surface charge and 30 mL of silver nanocrystals with positive surface charge (mass ratio of 1:0.2) prepared in step (2) are added to a 250 mL beaker at the same time (10 min), and the silver nanocrystals with different electronegativity are electrostatically self-assembled under magnetic stirring (rotation speed of 5000 rpm), and then centrifuged, washed with water, and vacuum dried to obtain a polyhedral micro-nano silver powder.
[0090] Example 3
[0091] (1) Same as step (1) of Example 1;
[0092] (2) Same as step (2) of Example 1;
[0093] (3) 50 mL of silver nanocrystals with negative charges on the surface and 150 mL of silver nanocrystals with positive charges on the surface (mass ratio of 1:3) prepared in step (2) are added to a 250 mL beaker at the same time (10 min), and the silver nanocrystals with different electronegativity undergo electrostatic self-assembly under magnetic stirring (rotation speed of 5000 rpm), and then centrifuged, washed with water, and vacuum dried to obtain a micro-nano silver powder with a lamellar structure.
[0094] Example 4
[0095] (1) Preparation of ultra-small silver nanocrystals:
[0096] Add 50 mg of polyethylene glycol, 1.92 g of ethylene glycol and 1.7 g of AgNO3 to 200 mL of deionized water and continue stirring at room temperature until completely dissolved. Then, heat the mixed solution to boiling and quickly add 200 μL of 0.3 mol L -1 Ascorbic acid solution was used to initiate the reduction reaction, and the stirring was continued for 1 hour to obtain an ultra-small silver nanocrystal solution;
[0097] (2) Surface charge modification of silver nanocrystals:
[0098] Measure 200 mL of the silver nanocrystal solution in step (1), add about 1 mL of stearic acid solution to adjust the pH of the solution to 3, and continue stirring for 1 hour to obtain silver nanocrystals with negative charges on the surface; similarly measure 200 mL of the silver nanocrystal solution in step (1), add about 1 mL of triethylamine solution to adjust the pH of the solution to 9, and continue stirring for 1 hour to obtain amine silver nanocrystals with positive charges on the surface;
[0099] (3) Assembly and preparation of micro-nano silver powder:
[0100] 100 mL of the silver nanocrystal solution with negative surface charge prepared in step (2) and 100 mL of the silver nanocrystal solution with positive surface charge (mass ratio of 1:1) were added into a 250 mL beaker at the same flow rate (10 mL / min), and the silver nanocrystals with different electronegativity underwent electrostatic self-assembly under magnetic stirring (rotation speed of 2000 rpm), and then centrifuged, washed with water, and vacuum dried to obtain spherical micro-nano silver powder.
[0101] Example 5
[0102] (1) Preparation of ultra-small silver nanocrystals:
[0103] Add 50 mg of polyvinyl alcohol, 1.92 g of hydrogen peroxide and 1.7 g of AgNO3 to 200 mL of deionized water and continue stirring at room temperature until completely dissolved. Then, heat the mixed solution to boiling and quickly add 200 μL of 0.1 mol L -1 Ascorbic acid solution was used to initiate the reduction reaction, and the stirring was continued for 1 hour to obtain an ultra-small silver nanocrystal solution;
[0104] (2) Surface charge modification of silver nanocrystals:
[0105] Measure 200 mL of the silver nanocrystal solution in step (1), add about 1 mL of lauric acid solution thereto to adjust the pH of the solution to 5, and continue stirring for 1 hour to obtain silver nanocrystals with negative charges on the surface; similarly measure 200 mL of the silver nanocrystal solution in step (1), add about 1 mL of triethanolamine solution thereto to adjust the pH of the solution to 11, and continue stirring for 1 hour to obtain amine silver nanocrystals with positive charges on the surface;
[0106] (3) Assembly and preparation of micro-nano silver powder:
[0107] 100 mL of the silver nanocrystal solution with negative surface charge prepared in step (2) and 100 mL of the silver nanocrystal solution with positive surface charge (mass ratio of 1:1) were added into a 250 mL beaker at the same flow rate (100 mL / min), and the silver nanocrystals with different electronegativity were electrostatically self-assembled under magnetic stirring (rotation speed of 10000 rpm), and then centrifuged, washed with water, and vacuum dried to obtain spherical micro-nano silver powder.
[0108] The test method and results are as follows:
[0109] 1) TEM photos of ultra-small silver nanocrystals prepared in Example 1 are as follows Figure 2 As shown, the crystallite size is about 20 nm, the shape is “rugby ball” and the density is high;
[0110] 2) The XRD pattern of the micro-nano silver powder prepared in Example 1 is as follows: Figure 3 As shown in the figure, the diffraction peak intensity is high, proving that it has good crystallization performance and high purity. The half-peak width of the diffraction peak is 0.015 rad, and the grain size is 9.19 nm calculated by the formula;
[0111] 3) The scanning electron microscope images of the micro-nano silver powder prepared in Examples 1 to 5 are as follows: Figure 4 , Figure 5 , Figure 6 , Figure 7 and Figure 8 As shown, the micro-nano silver powders of Examples 1, 4, and 5 are spherical, the micro-nano silver powder of Example 2 is polyhedral, and the micro-nano silver powder of Example 3 is a lamellar structure, and has good dispersibility and uniform size;
[0112] 4) The spherical micro-nano silver powder obtained in Example 1 was subjected to a sintering test at 140°C. Fig. 9 This is a scanning electron microscope image after sintering at 140°C for 30 minutes. It can be seen that the spherical nanosilver begins to stick together after sintering, indicating that it has high sintering activity.
[0113] Comparative Example 1
[0114] Add 50 mg of polyethylene glycol and 1.7 g of AgNO3 to 200 mL of deionized water and continue stirring at room temperature until completely dissolved. Then, quickly add 200 μL of 0.5 mol L -1 The reduction reaction was initiated by adding hydrazine hydrate solution, and stirring was continued for 1 hour, followed by centrifugation, water washing and vacuum drying to obtain submicron silver powder with a spherical structure.
[0115] The test method and results are as follows:
[0116] 1) The XRD pattern of the silver powder prepared in Comparative Example 1 is as follows Fig.10 As shown, the weaker XRD diffraction peaks indicate that its crystallization performance is general, the half-peak width of the diffraction peak is 0.006rad, and the grain size is 21.98nm calculated by the formula;
[0117] 2) The scanning electron microscope image of the silver powder prepared in Comparative Example 1 is as follows Fig.11 As shown, it can be seen that it presents a spherical shape, poor morphology, different sizes and uneven dispersion;
[0118] 3) The spherical nano silver powder obtained in Comparative Example 1 was subjected to sintering tests at 140°C and 180°C respectively. Fig.12 This is a scanning electron microscope image after sintering at 140°C for 30 minutes. Fig.13 This is a scanning electron microscope image after sintering at 180°C for 30 minutes. It can be seen that the spherical nanosilver only shows adhesion after sintering at 180°C, indicating that its sintering activity is low.
[0119] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0120] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0121] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing micro-nano silver powder, characterized in that: include: preparing a silver nanocrystal solution; Mixing the silver nanocrystal solution with an acidic regulator to obtain a silver nanocrystal solution with a negative charge; The silver nanocrystal solution is mixed with an alkaline regulator to obtain a silver nanocrystal solution with a positive charge; The negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution are mixed to obtain the micro-nano silver powder.
2. The method according to claim 1, characterized in that The morphology of the micro-nano silver powder includes at least one of a spherical structure, a cubic structure, a polyhedral structure, and a lamellar structure; and / or The mass ratio of the negatively charged silver nanocrystals to the positively charged silver nanocrystals is 1:0.2-3.
3. The method according to claim 1, characterized in that Satisfy at least one of the following conditions: The pH of the negatively charged silver nanocrystal solution is 3 to 5; The concentration of the negatively charged silver nanocrystal solution is 1 g / L to 5 g / L; The pH of the positively charged silver nanocrystal solution is 9 to 11; The concentration of the positively charged silver nanocrystal solution is 1 g / L to 5 g / L; The acidity regulator includes at least one of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, caprylic acid, nonanoic acid, capric acid, tartaric acid, oleic acid, ricinoleic acid, linoleic acid, stearic acid, palmitic acid, myristic acid, lauric acid, lactic acid, fumaric acid, and uric acid; The alkaline regulator includes at least one of ammonia water and an organic amine, and the organic amine includes at least one of ethylenediamine, dodecylamine, hexadecylamine, octadecylamine, triethylamine, and triethanolamine.
4. The method according to claim 1, characterized in that: The silver nanocrystal solution is prepared by the following steps: The silver nitrate aqueous solution, the dispersant and the reducing agent are mixed, and the obtained mixture is subjected to a reduction reaction to obtain the silver nanocrystal solution.
5. The method according to claim 4, characterized in that The dispersant comprises at least one of polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol; and / or The reducing agent comprises at least one of citric acid, sodium citrate, ethylene glycol, formaldehyde, and hydrogen peroxide, wherein the concentration of the solution prepared by the reducing agent is 0.1 mol / L to 0.5 mol / L; and / or The reaction temperature of the reduction reaction is 25° C. to 100° C., and the reaction is preferably carried out by heating to boiling state at normal pressure.
6. The method according to claim 1, characterized in that Mixing the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution comprises: adding the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution into a reaction container at the same time and stirring; and / or The addition rates of the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution are independently 10 mL / min to 100 mL / min; and / or The stirring speed of the negatively charged silver nanocrystal solution and the positively charged silver nanocrystal solution is 2000 rpm to 10000 rpm.
7. A micro-nano silver powder, characterized in that: The invention is prepared by the method according to any one of claims 1 to 6.
8. The micro-nano silver powder according to claim 7, characterized in that: The particle size of the micro-nano silver powder is 100nm to 500nm; and / or The specific surface area of the micro-nano silver powder is 0.8 m 2 / g~1.2m 2 / g.
9. A conductive paste, characterized in that: Contains the micro-nano silver powder according to any one of claims 7 to 8.
10. A battery, characterized in that: The invention comprises a metal electrode, wherein the metal electrode comprises the micro-nano silver powder according to any one of claims 7 to 8 or is prepared from the conductive paste according to claim 9.